A polyaryletherketone copolymer, a preparation method and application thereof

CN121673552BActive Publication Date: 2026-11-03JILIN ZHONGYAN HIGH PERFORMANCE PLASTIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610030075.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-09
Publication Date
2026-11-03
Estimated Expiration
2046-01-09

AI Technical Summary

Technical Problem

现有聚芳醚酮材料熔点高,难以适配FDM设备和激光焊接工艺,导致成型稳定性差,难以满足航空航天等高端制造领域的应用需求。

Method used

By introducing repeating units with rigid cyclic structures, the molar ratio and molecular weight of polyaryletherketone copolymers are controlled, the melting point is reduced, and the melting range is optimized, ensuring stable forming of the material in FDM equipment and laser welding processes.

Benefits of technology

Significantly reduces the melting point to a maximum of 312°C, the melting range to a maximum of 23°C, and increases the glass transition temperature to at least 150°C, ensuring the structural stability of the material at high temperatures, improving the material's processing fluidity and mechanical properties, and making it suitable for 3D printing and laser welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121673552B_ABST
    Figure CN121673552B_ABST
Patent Text Reader

Abstract

The present application relates to a polyaryletherketone copolymer and its preparation method and application. Specifically, the polyaryletherketone copolymer satisfies the following properties: 1) the polyaryletherketone copolymer consists essentially of repeating units of formula I: OPhOPhCOPh (I), and repeating units of formula II: OPhPhOPhCOPh (II), and the molar ratio of the repeating units of formula I: the repeating units of formula II is 50:50 to 90:10, preferably 60:40 to 89:11, more preferably 60:40 to 85:15; and 2) the melting point of the polyaryletherketone copolymer is at most 332℃, preferably at most 325℃, more preferably at most 320℃, even more preferably at most 315℃, most preferably at most 312℃. The polyaryletherketone copolymer according to the present application has a relatively low melting point, a relatively high glass transition temperature, a short melting range and a high tensile strength retention rate, and is suitable for use in the fields of prepreg, fused deposition 3D printing and laser welding, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of polymer materials technology, and relates to a polyaryletherketone copolymer, and more specifically to a polyaryletherketone copolymer with a low melting point, its preparation method and application. Background Technology

[0002] 3D printing technology, also known as additive manufacturing, is based on the principle of layer-by-layer manufacturing, where materials are added one by one to create a three-dimensional solid. This technology includes a series of different processes, such as selective laser sintering (SLS), stereolithography (SLA), and fused deposition modeling (FDM). Among them, FDM is one of the most widely used processes. Its principle is to heat thermoplastic polymer materials to a molten state, extrude thin layers with contoured shapes through a nozzle, and then stack them layer by layer to finally form the product.

[0003] Laser welding technology uses a high-energy-density laser beam to directly irradiate the surface of the material to be welded, causing the material to melt rapidly in a localized area (or even vaporize in a small amount) to form a molten pool; after the molten pool cools and solidifies, the separated materials can be "bonded together" to achieve structural connection.

[0004] Due to the high requirements for heat resistance and processing fluidity, the variety of polymer materials currently available on the market that are compatible with fused deposition modeling (FDM) and laser welding technologies is relatively limited. Traditional specialty engineering plastics (such as polyaryletherketones, PAEK) possess comprehensive advantages such as high heat resistance, radiation resistance, corrosion resistance, good dimensional stability, and excellent electrical properties, and have been widely used in high-end fields such as national defense, military, aerospace, electronics, petrochemicals, medical and health, and automobiles since their introduction. However, it should be noted that conventional polyaryletherketones have relatively high melting points (e.g., PEEK has a melting point of approximately 343°C), resulting in rapid crystallization during processing, poor interlayer bonding, which is unfavorable for molding, and they are usually difficult to directly adapt to FDM equipment and laser welding processes.

[0005] Therefore, fields such as 3D printing and laser welding still require polyaryletherketones (PAEKs) with further performance improvements, especially in lowering the melting point to adapt to conventional processing equipment and improve molding stability, while retaining the original heat resistance and mechanical properties. Breakthroughs in this area would significantly advance the application of PAEKs in high-end manufacturing, such as meeting the integrated 3D printing needs of complex PAEK components in the aerospace field, or solving high-precision laser welding challenges. Summary of the Invention

[0006] This application provides a polyaryletherketone copolymer, which satisfies the following properties: 1) The polyaryletherketone copolymer is substantially composed of the following: Repeating unit of Equation I: O Ph O Ph CO Ph (I), and Repeating unit of formula II containing a rigid ring structure: O Ph Ph O Ph CO Ph (II), and The molar ratio of the repeating units of Formula I to the repeating units of Formula II is 50:50 to 90:10, preferably 60:40 to 89:11, more preferably 60:40 to 85:15; and 2) The melting point of the polyaryletherketone copolymer is at most 332°C, preferably at most 325°C, more preferably at most 320°C, even more preferably at most 315°C, and most preferably at most 312°C.

[0007] In some embodiments according to this application, the rigid ring structure of the repeating unit of Formula II is derived from one or more of 2,2'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 1,4-naphthol, 1,5-naphthol, 2,3-naphthol, 2,6-naphthol, 2,7-naphthol, 2,2-bis(4-hydroxyphenyl)propane, and 4,4'-dihydroxydiphenyl sulfone, preferably derived from one or more of 2,2'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 1,4-naphthol, 1,5-naphthol, 2,6-naphthol, and 2,7-naphthol, more preferably derived from 4,4'-dihydroxybiphenyl.

[0008] In some embodiments according to this application, the glass transition temperature of the polyaryletherketone copolymer is at least 150°C, preferably at least 155°C, and more preferably at least 160°C.

[0009] In some embodiments according to this application, the number-average molecular weight (Mn) of the polyaryletherketone copolymer is in the range of 15,000 to 45,000, and the molecular weight is determined by gel permeation chromatography (GPC).

[0010] In some embodiments according to this application, the melting range of the polyaryletherketone copolymer is at most 43°C, preferably at most 35°C, more preferably at most 30°C, even more preferably at most 25°C, and most preferably at most 23°C.

[0011] In some embodiments according to this application, the repeating unit of formula I has a structural formula shown in any one of formulas (I-1) to (I-4): (I-1), (I-2) (I-3) (I-4) The repeating unit of formula II has a structure shown in any one of the following formulas (II-1) to (II-7): (II-1) (II-2) (II-3) (II-4) (II-5) (II-6) (II-7).

[0012] In some embodiments according to this application, the tensile strength of the polyaryletherketone copolymer is at least 75 MPa, preferably at least 80 MPa, and more preferably at least 85 MPa, as determined according to GB / T 1040.2-2022.

[0013] Another aspect of this application provides a method for preparing the above-mentioned polyaryletherketone copolymer, the method comprising the following steps: i) Under an inert atmosphere and in the presence of alkali metal carbonates, dihalobenzophenone undergoes nucleophilic condensation polymerization with a bisphenol derivative containing a rigid cyclic structure to obtain oligomer A; then ii) Under an inert atmosphere and in the presence of an alkali metal carbonate, oligomer A obtained in step i) is slowly added to a mixture of dihydroxybenzene, solvent, and dihalobenzophenone, and the reaction continues; then iii) After the reaction is completed, the mixture is cooled and purified to obtain the polyaryletherketone copolymer.

[0014] In some embodiments according to this application, step i) is performed at a temperature of at least 220°C, involving nucleophilic polycondensation.

[0015] In some embodiments according to this application, in step i), there is at least 70% by weight of solvent relative to the total amount of material, preferably at least 75% by weight of solvent, and more preferably at least 80% by weight of solvent.

[0016] In some embodiments according to this application, the number average molecular weight of oligomer A obtained in step i) is at most 18,000, preferably at most 16,000.

[0017] In some embodiments according to this application, the polydispersity index of oligomer A obtained in step i) is at most 2.3, preferably at most 2.25, and more preferably at most 2.2.

[0018] In some embodiments of this application, the glass transition temperature of oligomer A obtained in step i) is at least 160°C, preferably at least 165°C, and more preferably at least 170°C.

[0019] A third aspect of this application provides a method for melt deposition molding, which uses a polyaryletherketone copolymer according to the first aspect of this application or a polyaryletherketone copolymer prepared by the method according to the second aspect of this application for melt deposition molding.

[0020] The fourth aspect of this application provides printing materials, particularly 3D printing materials, or laser-weldable materials, comprising polyaryletherketone copolymers according to the first aspect of this application or polyaryletherketone copolymers prepared by the method according to the second aspect of this application.

[0021] The fifth aspect of this application provides the use of polyaryletherketone copolymers according to the first aspect of this application or polyaryletherketone copolymers prepared by the method according to the second aspect of this application for the preparation of printing materials, particularly 3D printing materials, or laser-weldable materials.

[0022] The sixth aspect of this application provides a prepreg prepared from a polyaryletherketone copolymer according to the first aspect of this application or from a polyaryletherketone copolymer prepared by the method according to the second aspect of this application.

[0023] The printing materials, laser-weldable materials, and prepregs of this application include the polyaryletherketone copolymers provided in this application, and therefore have at least the same advantages as the polyaryletherketone copolymers. Attached Figure Description

[0024] Figure 1 A DSC test diagram according to Embodiment 1 of this application is schematically shown. Detailed Implementation

[0025] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the polyaryletherketone copolymer of this application, its preparation method, and related applications. However, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of essentially the same structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0026] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0027] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0028] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0029] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0030] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0031] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0032] Unless otherwise specified, in this application, the terms "first," "second," "third," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.

[0033] In this application, the terms "multiple", "various", etc., refer to two or more kinds.

[0034] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.

[0035] Unless otherwise stated, the values ​​of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application. Unless otherwise stated, the test temperature is 25°C.

[0036] The term "halogen atom" includes fluorine atoms, chlorine atoms, bromine atoms, etc.

[0037] Polyaryletherketone (PAEK) possesses comprehensive advantages such as high heat resistance, radiation resistance, corrosion resistance, good dimensional stability, and excellent electrical properties. Since its introduction, it has been widely used in high-end fields such as national defense, military industry, aerospace, electronics and information technology, petrochemicals, medical and health care, and automobiles. However, conventional PAEK has a relatively high melting point (e.g., PEEK's melting point is approximately 343℃), making it difficult to use in FDM and laser welding processes.

[0038] Therefore, 3D printing technology and laser welding still require further improvements in the performance of polyaryletherketones (PAEKs), especially in lowering the melting point to adapt to conventional processing equipment, improving molding stability, and retaining the original heat resistance and mechanical properties. Breakthroughs in this area would significantly advance the application of PAEKs in high-end manufacturing, such as meeting the integrated 3D printing needs of complex PAEK components in the aerospace field, or solving high-precision laser welding challenges.

[0039] To address the aforementioned issues, the inventors of this application conducted extensive experiments and in-depth research, and surprisingly discovered that by introducing repeating units containing rigid cyclic structures into the matrix polymer, the presence of the rigid structure hinders chain segment movement. The repeating units of Formula I and Formula II in a specific molar ratio enable the regulation of material properties, resulting in a significant reduction in the melting point of the obtained copolymer, greatly narrowing the gap with the processing temperature of FDM equipment, reducing the difficulty of melt molding, and greatly expanding the application fields of polyaryletherketone.

[0040] Therefore, a first aspect of the present application provides a polyaryletherketone copolymer that satisfies the following properties: 1) The polyaryletherketone copolymer is substantially composed of the following: Repeating unit of Equation I: O Ph O Ph CO Ph (I), and Repeating unit of formula II containing a rigid ring structure: O Ph Ph O Ph CO Ph (II), and The molar ratio of the repeating units of Formula I to the repeating units of Formula II is 50:50 to 90:10, preferably 60:40 to 89:11, more preferably 60:40 to 85:15, even more preferably 60:40 to 82:18, even more preferably 65:35 to 82:18, and most preferably 65:35 to 80:20; and 2) The melting point of the polyaryletherketone copolymer is at most 332°C, preferably at most 325°C, more preferably at most 320°C, even more preferably at most 315°C, and most preferably at most 312°C.

[0041] In the context of this application, "consistent with" means that, in addition to the listed components, the other components are present in an amount of up to 5% by weight, preferably up to 3% by weight, and more preferably up to 1.5% by weight.

[0042] In some embodiments according to this application, the rigid ring structure of the repeating unit of Formula II is derived from one or more of 2,2'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 1,4-naphthol, 1,5-naphthol, 2,3-naphthol, 2,6-naphthol, 2,7-naphthol, 2,2-bis(4-hydroxyphenyl)propane, and 4,4'-dihydroxydiphenyl sulfone, preferably derived from one or more of 2,2'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 1,4-naphthol, 1,5-naphthol, 2,6-naphthol, and 2,7-naphthol, more preferably derived from 4,4'-dihydroxybiphenyl.

[0043] In some embodiments according to this application, the glass transition temperature of the polyaryletherketone copolymer is at least 150°C, preferably at least 155°C, and more preferably at least 160°C.

[0044] This application introduces repeating units with rigid cyclic structures into the matrix polymer. The presence of the rigid structure hinders chain segment movement, and the specific molar ratio of repeating units of Formula I and Formula II enables the regulation of material properties, resulting in a significant reduction in the melting point of the obtained copolymer. For example, the melting point of the obtained copolymer is at most 332°C, preferably at most 325°C, more preferably at most 320°C, even more preferably at most 315°C, and most preferably at most 312°C, for example, 330°C, 325°C, 320°C, 315°C, 312°C, 310°C, 305°C, or within any two of the above values. The reduction in melting point significantly narrows the gap with the processing temperature of FDM equipment, reducing the difficulty of melt molding; at the same time, the glass transition temperature is increased, for example, the glass transition temperature of the obtained copolymer is at least 150°C, preferably at least 155°C, more preferably at least 160°C, ensuring that the material can maintain structural stability at high temperatures and avoiding the impact of thermal deformation on performance.

[0045] In addition, molecular weight is an important parameter affecting the processing fluidity and mechanical strength of polymers. This application controls the monomer ratio and polymerization reaction conditions to make the molecular weight of polyaryletherketone copolymer fall within the target range.

[0046] In some embodiments of this application, the number average molecular weight (Mn) of the polyaryletherketone copolymer is in the range of 15,000 to 45,000, preferably in the range of 20,000 to 45,000, and more preferably in the range of 25,000 to 45,000. For example, the number average molecular weight of the polyaryletherketone copolymer can be 20,000, 21,000, 22,000, 23,000, 24,000, 25,000, 26,000, 27,000, 28,000, 29,000, 30,000, 31,000, 32,000, 33,000, 34,000, 35,000, 36,000, 37,000, 38,000, 39,000, 40,000, 41,000, 42,000, 43,000, 44,000, 45,000 or within any two of the above values.

[0047] In some embodiments according to this application, the weight-average molecular weight (Mw) of the polyaryletherketone copolymer is in the range of 60,000 to 130,000, preferably in the range of 70,000 to 120,000, and more preferably in the range of 70,000 to 115,000. Exemplarily, the weight-average molecular weight of the polyaryletherketone copolymer can be 60,000, 65,000, 70,000, 75,000, 80,000, 85,000, 90,000, 95,000, 100,000, 105,000, 110,000, 115,000, 120,000, 125,000, 130,000, or within any two of the above values.

[0048] Number-average molecular weight and weight-average molecular weight were determined by gel permeation chromatography (GPC).

[0049] The above molecular weight range avoids insufficient mechanical strength of materials due to excessively low molecular weight, such as easy breakage of welded joints; at the same time, it prevents excessively high molecular weight from causing excessively high melt viscosity, such as difficulty in extrusion of FDM nozzles and easy clogging; moreover, the above molecular weight range further ensures the impact resistance and fatigue resistance of materials, ensuring that 3D printed parts are not prone to cracking during long-term use, and that the joints after laser welding can withstand dynamic loads.

[0050] By moderately adjusting the regularity of the molecular chain through a rigid ring structure, the melting temperature range (i.e., melting range) of the material is effectively narrowed. In some embodiments according to this application, the melting range of the polyaryletherketone copolymer is at most 43°C, preferably at most 35°C, more preferably at most 30°C, even more preferably at most 25°C, and most preferably at most 23°C, for example 43°C, 40°C, 35°C, 34°C, 33°C, 32°C, 31°C, 30°C, 29°C, 28°C, 27°C, 26°C, 25°C, 24°C, 23°C, 22°C, 21°C, 20°C, 19°C, 18°C, 17°C, or within any two of the above values.

[0051] In this article, melting range refers to the temperature range that a material experiences from the initial melting (initial melting) to complete melting (final melting). The melting range of a polymer directly determines its processing adaptability, product quality stability, and applications. Polymers with narrow melting ranges have fast melting and cooling rates, requiring precise control of processing temperatures and are suitable for high-speed molding; polymers with wide melting ranges have high tolerance for temperature regulation errors, are suitable for processes requiring gradient temperature control, and avoid problems such as local overheating degradation or incomplete melting.

[0052] Therefore, melting range characteristics are crucial to the processing stability of materials: compared with wide melting range materials, the copolymer according to this application has a relatively narrow melting range, which can quickly transform from a solid state to a uniform molten state during heating, avoiding the situation of "partially melted and partially still solid particles", reducing the risk of FDM nozzle clogging; at the same time, during laser welding, the relatively narrow melting range of the copolymer according to this application can ensure that the material melts synchronously in the heat-affected zone, avoiding decomposition due to local overheating, or the formation of incomplete fusion defects due to insufficient melting.

[0053] Based on the optimization of melting point, glass transition temperature, melting range and molecular weight, the polyaryletherketone copolymer according to this application is not only suitable for the prepreg field, but also suitable for the fields of fused deposition modeling 3D printing and laser welding.

[0054] In 3D printing, a lower melting point, narrower melting range, and appropriate molecular weight result in more stable material melt flow. This allows for smooth passage through the nozzle, avoiding blockage by localized high-viscosity particles, and enables rapid solidification after extrusion (the relatively narrow melting range shortens solidification time), reducing interlayer adhesion defects and improving the mechanical uniformity of the printed parts. In laser welding, the synergistic effect of a lower melting point and a relatively narrow melting range significantly reduces the risk of welding heat damage. The lower melting point reduces the laser energy input requirement, while the relatively narrow melting range ensures uniform melting of the material within the set temperature range, avoiding localized overheating and decomposition. An appropriate molecular weight also enhances the interlayer bonding strength of the weld joint. Excessively high molecular weight leads to poor molten material flow, easily resulting in air bubbles or unfused areas in the weld. Conversely, excessively low molecular weight results in insufficient molecular chain entanglement at the weld. The molecular weight range of this application ensures that the molten copolymer flows fully and spreads uniformly at the weld, forming a dense and high-strength bonding interface, fundamentally solving the cracking and delamination problems that easily occur in traditional PAEK welding.

[0055] Therefore, the polyaryletherketone copolymer of this application, through multi-dimensional optimization of melting point, glass transition temperature, melting range, and molecular weight, effectively fills the performance gap of existing materials in the fields of 3D printing and laser welding, and has greater application advantages than conventional PAEK. This was unforeseen before this application.

[0056] In some embodiments according to this application, the repeating unit of formula I has the following structural formula (any one of (I-1) to (I-4): (I-1), (I-2) (I-3) (I-4) Preferably, it has the structural formula shown in (I-1); the repeating unit of formula II has the structural formula shown in any one of the following formulas (II-1) to (II-7): (II-1) (II-2) (II-3) (II-4) (II-5) (II-6) (II-7) Preferably, the repeating unit of formula II has the structural formula shown in formula (II-1).

[0057] The introduction of rigid ring structures effectively compensates for the mechanical losses that may be caused by low-melting-point modification, providing support for the performance optimization of polyaryletherketone copolymers. Its unique conjugated structure and steric hindrance effect can not only suppress the disordered stacking and thermal motion of molecular chains, effectively offsetting the mechanical attenuation problem that may be caused by the increase in molecular chain flexibility during low-melting-point modification, but also endow the material with excellent structural regularity and resistance to deformation by enhancing intermolecular forces, thus giving the material excellent tensile strength.

[0058] In some embodiments of this application, the tensile strength of the polyaryletherketone copolymer is determined according to GB / T 1040.2-2022 (National Standard for Determination of Tensile Properties of Plastics) to be at least 75 MPa, preferably at least 80 MPa, and more preferably at least 85 MPa. Such tensile strength ensures that the 3D printed part can withstand the load in actual use, and the joint strength after laser welding is not too low, avoiding failure due to insufficient mechanical properties.

[0059] Such high strength provides a guarantee for the practical application of the material: in 3D printing scenarios, whether it is industrial parts, structural supports or functional components, it can stably withstand the mechanical stress in actual use processes such as assembly fastening, working loads, and environmental vibrations, avoiding failure phenomena such as cracking, deformation, and breakage; in laser welding processes, thanks to the material's good welding compatibility, the molecular chain fusion degree of the weld joint is high, and its tensile strength can be stably maintained, ensuring the integrity and reliability of the welded structure, fully meeting the stringent requirements of mechanical stability of parts in the automotive, electronics, aerospace and other fields, and completely avoiding problems such as shortened product life and safety hazards caused by insufficient mechanical properties.

[0060] Another aspect of this application provides a method for preparing the above-mentioned polyaryletherketone copolymer, the method comprising the following steps: i) Under an inert atmosphere and in the presence of alkali metal carbonates, dihalobenzophenone undergoes nucleophilic condensation polymerization with a bisphenol derivative containing a rigid cyclic structure to obtain oligomer A; then ii) Under an inert atmosphere and in the presence of an alkali metal carbonate, oligomer A obtained in step i) is slowly added to a mixture of dihydroxybenzene, solvent, and dihalobenzophenone, and the reaction continues; then iii) After the reaction is completed, the mixture is cooled and purified to obtain the polyaryletherketone copolymer.

[0061] In some embodiments according to this application, the alkali metal carbonate comprises sodium carbonate or a mixture of sodium carbonate and potassium carbonate, preferably a mixture of sodium carbonate and potassium carbonate, wherein the molar ratio of the two is in the range of 40-60:1, preferably in the range of 45-55:1, for example 40:1, 41:1, 42:1, 43:1, 44:1, 45:1, 46:1, 47:1, 48:1, 49:1, 50:1, 51:1, 52:1, 53:1, 54:1, 55:1, 56:1, 57:1, 58:1, 59:1, 60:1 or within any two of the above values.

[0062] The essence of nucleophilic polycondensation is that a nucleophile (such as monomers containing hydroxyl or amino groups) undergoes substitution or elimination reactions with the functional groups of the substrate to form new covalent bonds, accompanied by the removal of small molecule byproducts. For the synthesis of the polyaryletherketone copolymer according to this application, the temperature for nucleophilic polycondensation in step i) is chosen to be at least 220°C, mainly based on the following requirements: breaking the hydrogen bonds and van der Waals forces between monomer molecules, reducing the viscosity of the reaction system, providing kinetic conditions for effective collisions of functional groups and directional growth of molecular chains; providing sufficient energy for the rapid removal of small molecule byproducts, avoiding the retention of byproducts in the reaction system, inhibiting reverse reactions, and ensuring that the polycondensation reaction proceeds fully towards the formation of a polymer of the predetermined molecular weight.

[0063] In some embodiments according to this application, step i) is performed at a temperature of at least 220°C, preferably at least 230°C, and more preferably at least 240°C. Furthermore, step i) is performed at a temperature of up to 350°C, preferably up to 325°C, and more preferably up to 305°C.

[0064] If the temperature is below 220℃, it will not only lead to insufficient monomer activation and a significant decrease in reaction rate, but may also cause end-group capping and hinder molecular chain growth due to incomplete removal of by-products, ultimately resulting in products with low molecular weight and substandard mechanical properties and thermal stability. If the temperature is too high (above 350℃), it may cause side reactions such as thermal degradation and cross-linking of polymer molecular chains, resulting in problems such as decreased mechanical properties and poor thermal stability of the product.

[0065] When the temperature for nucleophilic polycondensation in step i) is within the above range, the above temperature range can ensure the reaction efficiency and avoid excessive reaction or degradation of monomers at high temperatures. Therefore, the nucleophilic polycondensation reaction is more complete, the molecular chain growth rate is uniform, the molecular weight distribution is effectively controlled, and a narrow distribution oligomer with a polydispersity index (PDI) ≤ 2.3 is obtained. Moreover, the molecular chain structure is regular, the functional groups are intact, and it has high reactivity.

[0066] In some embodiments according to this application, an aromatic sulfone is used as a solvent during the nucleophilic polycondensation process. The aromatic sulfone is selected from one or more of diphenyl sulfone, dibenzothiophene dioxide, phenoxthiophene dioxide, and 4-phenylsulfonyl biphenyl, preferably diphenyl sulfone. Such a solvent has good solubility, can fully dissolve the reactant monomers and the resulting oligomers, avoids monomer aggregation or oligomer precipitation, and ensures that the reaction proceeds efficiently in a homogeneous system.

[0067] In step i), at least 70% by weight of solvent is present relative to the total feed amount, preferably at least 75% by weight, and more preferably at least 80% by weight. Preferably, in step i), 70% to 90% by weight of solvent is present relative to the total feed amount. Sufficient solvent can reduce the viscosity of the reaction system, improve the fluidity of molecular chains and the collision efficiency of functional groups, promote the full advancement of the polycondensation reaction, accelerate the removal of small molecule byproducts, and inhibit the occurrence of reverse reactions. Controlling the solvent weight within the above range can further improve the homogeneity of the reaction system, reduce local reaction rate differences, and help control the molecular weight distribution and structural regularity of the oligomers while ensuring that the viscosity of the reaction system is within an appropriate range, thereby reducing the solid content and obtaining oligomers with appropriate molecular weight and narrower distribution.

[0068] In some embodiments of this application, the dihalobenzophenone is one or more of 4,4'-difluorobenzophenone, 2,4'-difluorobenzophenone, 4,4'-dichlorobenzophenone, and 2,4'-dichlorobenzophenone, preferably 4,4'-difluorobenzophenone.

[0069] In some embodiments of this application, the bisphenol derivative containing a rigid cyclic structure is selected from one or more of 2,2'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 1,4-naphthol, 1,5-naphthol, 2,3-naphthol, 2,6-naphthol, 2,7-naphthol, 2,2-bis(4-hydroxyphenyl)propane, and 4,4'-dihydroxydiphenyl sulfone, preferably selected from one or more of 2,2'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 1,4-naphthol, 1,5-naphthol, 2,6-naphthol, and 2,7-naphthol, and more preferably selected from 4,4'-dihydroxybiphenyl.

[0070] In some embodiments according to this application, the dihydroxybenzene is hydroquinone, resorcinol, catechol, and 2-methyl-1,4-hydroquinone, preferably hydroquinone.

[0071] In some embodiments according to this application, the molar ratio of the dihydroxybenzene to the bisphenol derivative containing the rigid cyclic structure is 50:50 to 90:10, preferably 60:40 to 89:11, more preferably 60:40 to 85:15, even more preferably 60:40 to 82:18, even more preferably 65:35 to 82:18, and most preferably 65:35 to 80:20.

[0072] In some embodiments according to this application, the number-average molecular weight of oligomer A obtained in step i) is at most 18,000, preferably at most 16,000, and preferably at least 4,000, more preferably at least 4,500, and even more preferably at least 5,000, for example, 4,000, 4,500, 5,000, 6,000, 7,000, 8,000, 9,000, 10,000, 11,000, 12,000, 13,000, 14,000, 15,000, 16,000, or within any two of the above values. This molecular weight range is an important choice that balances the feasibility of subsequent processing with the performance of the final product.

[0073] If the number average molecular weight of oligomer A obtained in step i) is too low and the molecular chain is too short, oligomer A will react further in step ii), resulting in uneven distribution of chain segments in the final copolymer; if the number average molecular weight of oligomer A obtained in step i) is too high and the molecular chain is too long, the reactivity in step ii) may be insufficient, making it difficult to effectively participate in copolymerization, or the chain segments may be unevenly distributed, and the final product obtained may show melting point peaks in DSC testing (i.e., mixtures) or the mechanical strength, thermal stability and other properties may not meet expectations.

[0074] Oligomers with a number average molecular weight within the above range have good reactivity, which can ensure the full progress of subsequent polymerization reactions and the uniform arrangement of molecular chains during the molding process, thus laying the foundation for the performance stability of the final product.

[0075] In some embodiments according to this application, the polydispersity index (PDI) of oligomer A obtained in step i) is at most 2.3, preferably at most 2.25, more preferably at most 2.2, for example 2.3, 2.25, 2.2, 2.15, 2.1, 2.05, 2, 1.95, 1.9, 1.85, 1.8 or within any two of the above values.

[0076] In step i) of the nucleophilic polycondensation reaction, oligomers with a lower polydispersity index (PDI) can be obtained by controlling the reaction temperature and solvent dosage. A lower PDI indicates a more uniform molecular chain length in the oligomer, avoiding performance limitations caused by short-chain molecules or processing defects caused by long-chain molecule aggregation, and ensuring the segment regularity of the final copolymer. When the PDI is controlled below 2.3, the oligomer exhibits more consistent reactivity in subsequent reaction processes, resulting in a more uniform internal structure of the molded material and a significantly reduced range of fluctuations in mechanical properties such as tensile strength and impact toughness.

[0077] In some embodiments according to this application, the glass transition temperature of oligomer A obtained in step i) is at least 160°C, preferably at least 165°C, more preferably at least 170°C, for example 160°C, 165°C, 170°C, 175°C, 180°C or within any two of the above values.

[0078] The glass transition temperature (Tg) is the critical temperature at which a polymer transitions from a glassy state to a rubbery state. A Tg of at least 160°C ensures that oligomers can withstand certain high-temperature environments during subsequent processing and practical applications, avoiding problems such as deformation and softening caused by temperature increases. If the Tg of an oligomer is below 160°C, its thermal stability is insufficient, making it prone to thermal deformation during subsequent heating processing steps (such as secondary polymerization and molding), and may even lead to molecular chain degradation, affecting the performance of the final product.

[0079] The preparation method described in this application is a two-step prepolymerization-copolymerization method, which differs from the conventional one-step method. The conventional one-step method typically involves mixing all monomers, such as dihydroxybenzene and bisphenol derivatives with rigid cyclic structures, with solvents and catalysts in a single process, completing nucleophilic polymerization within a single temperature range. This process has an inherent, unavoidable drawback: the reactivity of different bisphenol monomers varies significantly. Dihydroxybenzene (such as hydroquinone) has higher reactivity due to its simple molecular structure and low steric hindrance, allowing it to rapidly undergo nucleophilic substitution reactions with dihaloaromatic monomers at lower temperatures, forming a large number of short-chain oligomers. Bisphenol derivatives with rigid cyclic structures (such as bisphenol monomers containing naphthalene rings or biphenyl groups) have lower reactivity due to the steric hindrance of their cyclic structures, requiring higher temperatures to overcome the reaction energy barrier and achieve effective polymerization.

[0080] In the one-step polymerization process, the polymerization of "highly reactive monomers reacting first and less reactive monomers reacting later" may result in a random and disordered distribution of the final polymer's molecular chain structure. This disordered structure is not conducive to the precise control of the polymer and cannot meet the stringent requirements of high-end applications for the thermal stability and mechanical properties of materials.

[0081] In contrast, the two-step method of this application balances the reactivity of different monomers through a prepolymerization-copolymerization strategy to achieve a periodic and regular arrangement of molecular chains.

[0082] First, during the prepolymerization stage, the bisphenol derivative containing a rigid cyclic structure is activated separately to form a structurally regular oligomer A with a number-average molecular weight precisely controlled to a maximum of 18,000, a polydispersity index (PDI) ≤ 2.3, and a glass transition temperature (Tg) ≥ 160℃. The end groups of oligomer A retain active functional groups (such as halogen atoms and hydroxyl groups), laying the foundation for subsequent copolymerization reactions with other monomers. Simultaneously, the rigid cyclic structure endows it with excellent thermal and structural stability.

[0083] In the copolymerization stage, the rigid oligomer A prepared in the prepolymerization stage is copolymerized with highly active dihydroxybenzene and dihalobenzophenone to obtain an alternating periodic copolymer with high molecular chain regularity and excellent crystallinity. It also has the high strength brought by the rigid structure and the moderate flexibility brought by the dihydroxybenzene segments.

[0084] This stepwise polymerization method fundamentally solves the problems of the one-step polymerization method, enabling the two structural units to be arranged in an orderly manner on the molecular chain, forming a regular periodic copolymer structure, rather than a randomly packed mixture. The crystallinity of polymers depends on the regularity of the molecular chain and the ability of the chain segments to stack. The periodic molecular chain structure obtained by the two-step method of this application has high regularity, reduces the steric hindrance in the chain segment stacking process, and makes it easier for the molecular chain to form ordered crystalline regions, thus significantly improving the crystallinity.

[0085] Therefore, the glass transition temperature (Tg) and heat distortion temperature of the final polymer are significantly improved, while the crystallization uniformity is enhanced. This avoids the fluctuation of mechanical properties caused by uneven crystallization in one-step products, ensuring that the material can maintain excellent tensile strength, rigidity and dimensional stability at high temperatures. It is suitable for applications with stringent requirements for crystallinity and thermal stability.

[0086] A third aspect of this application provides a method for melt deposition modeling, wherein melt deposition modeling is performed using a polyaryletherketone copolymer according to a first aspect of this application or a polyaryletherketone copolymer prepared by a method according to a second aspect of this application.

[0087] The fourth aspect of this application provides a printing material, particularly a 3D printing material, or a laser-weldable material, comprising a polyaryletherketone copolymer according to the first aspect of this application or a polyaryletherketone copolymer prepared by the method according to the second aspect of this application.

[0088] The fifth aspect of this application provides the use of polyaryletherketone copolymers according to the first aspect of this application or polyaryletherketone copolymers prepared by the method according to the second aspect of this application for the preparation of printing materials, particularly 3D printing materials, or laser-weldable materials.

[0089] A sixth aspect of this application provides a prepreg prepared from a polyaryletherketone copolymer according to a first aspect of this application or from a polyaryletherketone copolymer prepared by a method according to a second aspect of this application. In the context of this application, the term "prepreg" refers to a composition of a resin matrix and a reinforcement formed by impregnating a resin matrix with fibers or fabrics that serve as a continuous reinforcement, which is an intermediate material for manufacturing composite materials.

[0090] Example The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0091] Test method: 1) Number average molecular weight: The number average molecular weight of the oligomers or polymers prepared according to the embodiments and comparative examples of the present invention is based on gel chromatography and tested using a PL-220 gel chromatograph (GPC). 2) Melting point, glass transition temperature (Tg), melting range and crystallinity: obtained by DSC test according to ISO 11357, the specific heating steps are as follows; Step 1 involves heating the sample from 30°C to 400°C at a rate of 10°C / min to perform and record the initial thermal cycling. Step 2: Hold for 5 minutes; Step 3: Cool to 30°C at 10°C / min and hold for 5 minutes; Step 4: Reheat from 30°C to 400°C at a rate of 10°C / min; The built-in analysis program of the DSC instrument was used. Tg was obtained from the curve in step 1, and Tm, crystallinity, and melting range were obtained from the curve in step 3. The melting range is obtained by calculating the difference between the final melting point and the initial melting point. The initial melting point is where the right tangent line at the melting start point intersects with the left tangent line at the melting point; the final melting point is where the left tangent line at the melting end point intersects with the right tangent line at the melting point.

[0092] 3) Tensile strength: Tested by tensile testing machine according to GB / T 1040.2-2022. Part requirements: 1A / 1B type; Test conditions: tensile rate 20mm / min; gauge length 75mm.

[0093] Preparation Example 1: Preparation of PEEK 55.06 g (0.50 mol) hydroquinone, 109.10 g (0.50 mol) 4,4'-difluorobenzophenone, and 400 g diphenyl sulfone were sequentially added to a four-necked flask equipped with a mechanical stirrer and thermometer. After purging with nitrogen for 30 min, heating was initiated, and the temperature was raised to 150 °C. The reactants melted and dissolved, and then 60.39 g of anhydrous sodium carbonate and 1.60 g of anhydrous potassium carbonate were added. The temperature was maintained for 3 h. The temperature was then raised to 250 °C and maintained for 1 h. Finally, the temperature was raised to 320 °C and maintained for 1.5 h. The sample was poured into a stainless steel square pan for cooling. The crude reaction product was obtained by pulverization.

[0094] The crude product was repeatedly washed with acetone and water to remove the solvent diphenyl sulfone and inorganic salts, and finally dried at 150°C to obtain polymer powder.

[0095] The polymer is a polyether ether ketone (PEEK) polymer with Mn=25000-30000.

[0096] Preparation Example 2: Preparation of Oligomer A 93.11 g (0.50 mol) of 4,4'-dihydroxybiphenyl, 109.10 g (0.50 mol) of 4,4'-difluorobenzophenone, and 400 g of diphenyl sulfone were sequentially added to a four-necked flask equipped with a mechanical stirrer and a thermometer. After purging with nitrogen for 30 min, heating was started, and the temperature was raised to 150 °C. The reactants melted and dissolved, and then 60.39 g of anhydrous sodium carbonate and 1.60 g of anhydrous potassium carbonate were added. The temperature was maintained for 2 h. The temperature was then raised to 250 °C and maintained for 1 h. Finally, the temperature was raised to 300 °C and maintained for 2 h. The sample was then poured into a stainless steel square pan for cooling. The crude reaction product was obtained by pulverization.

[0097] The crude product was repeatedly washed with acetone and water to remove the solvent diphenyl sulfone and inorganic salts. Finally, it was dried at 150°C to obtain oligomer powder A1 with a purity higher than 99%.

[0098] Repeat the above steps, adjusting the diphenyl sulfone content to 800g, to obtain oligomer powder A2 with a purity higher than 99%.

[0099] The number-average molecular weight of the oligomers was determined by GPC, and their glass transition temperature was determined by DSC. The results are shown in Table 1 below.

[0100] Table 1: Molecular weight and glass transition temperature of oligomer A As shown in Table 1, oligomer A1 is a biphenyl-type polyether ether ketone with a normal molecular weight, while oligomer A2 is a biphenyl-type polyether ether ketone with a lower molecular weight. Increasing the amount of diphenyl sulfone diluted the components, allowing them to react in a more dilute state, which makes it easier to obtain biphenyl-type polyether ether ketones with a narrower molecular weight distribution and a lower number-average molecular weight.

[0101] Copolymer preparation by prepolymer-copolymer method A certain amount of hydroquinone, 4,4'-difluorobenzophenone, and 400g of diphenyl sulfone were sequentially added to a four-necked flask equipped with a mechanical stirrer and thermometer. After purging with nitrogen for 30 minutes, heating was initiated, raising the temperature to 150℃. The reactants melted and dissolved, and then a certain amount of anhydrous sodium carbonate and anhydrous potassium carbonate were added. A certain amount of oligomer A1 or A2 powder was slowly added, and the temperature was gradually increased to 250℃ for prepolymerization for 1.0 h. The temperature was then raised to 300℃ and held for 1.0 h. Finally, the temperature was raised to 320℃ for copolymerization for 0.5 h. The sample was then poured into a stainless steel square pan for cooling. The crude reaction products C1-C6 were obtained by pulverization.

[0102] The crude product C1-C6 was repeatedly washed with acetone and water to remove the solvent diphenyl sulfone and inorganic salts, and finally dried at 150°C to obtain copolymer powder C1-C6.

[0103] The dosage of each component is shown in Table 2 below.

[0104] Table 2: Feeding table for copolymers prepared by prepolymer-copolymer method Comparative Example 2: One-step preparation of copolymers 44.04 g (0.40 mol) hydroquinone, 18.62 g (0.10 mol) 4,4'-dihydroxybiphenyl, 109.10 g (0.50 mol) 4,4'-difluorobenzophenone, and 351.26 g diphenyl sulfone were added sequentially to a four-necked flask equipped with a mechanical stirrer and thermometer. After purging with nitrogen for 30 min, heating was started, and the temperature was raised to 150 °C. The reactants melted and dissolved, and then 60.39 g of anhydrous sodium carbonate and 1.60 g of anhydrous potassium carbonate were added. The temperature was maintained for 2 h; the temperature was raised to 250 °C and maintained for 1 h; the temperature was raised to 300 °C and maintained for 1 h; the temperature was raised to 320 °C and maintained for 0.5 h. The sample was then poured into a stainless steel square pan for cooling. The crude reaction product D was obtained by pulverization.

[0105] The crude product D was repeatedly washed with acetone and water to remove the solvent diphenyl sulfone and inorganic salts, and finally dried at 150°C to obtain polymer powder D.

[0106] Polymer D is a copolymer in which the molar ratio of repeating units of Formula I to repeating units of Formula II is 80:20.

[0107] Comparative Examples 3 and 4: Preparation of PEEK / PEI blends The PEEK obtained in the preparation example and the commercially available PEI were baked in an oven at 120°C for 1 hour, respectively. Then, they were accurately weighed at mass ratios of 75 / 25 and 25 / 75, respectively, and melt-extruded at a temperature of 380°C to obtain PEEK / PEI blends E1 and E2. The PEI resin was sourced from Saudi Basic Industries Corporation (SABIC), model SABIC ULTEM 1010 PEI.

[0108] The obtained copolymers C1-C6 and copolymer D, blends E1 and E2, and commercially available PEI (SABIC ULTEM 1010 PEI) were tested according to the methods described in the test section. The results are shown in Table 3 below.

[0109] Table 3: Performance Tests of the Products As shown in Table 3, compared to the PEEK polymer in the preparation example, copolymers C1-C6 and D all have lower melting points and higher glass transition temperatures, indicating that these copolymers maintain good heat resistance while having lower processing temperatures. This change may be attributed to the introduction of rigid cyclic structural units, which increases the glass transition temperature and lowers the melting point, resulting in a significant reduction in processing temperature.

[0110] Compared to the PEEK polymer in the preparation examples, the crystallinity and tensile strength of copolymers C1-C6 and D are reduced. This is mainly because the introduction of rigid structures disrupts the regularity of the molecular chains to some extent, thereby reducing crystallinity. In processing applications, it is generally desirable to maintain higher crystallinity while lowering the melting point, as higher crystallinity often corresponds to better mechanical properties (such as tensile strength). To this end, this application further optimizes the two-step prepolymer-copolymerization method: as shown in Examples 1-4, a block copolymer structure is formed by introducing a rigid-structured oligomer A with a low molecular weight, narrow molecular weight distribution (Mn≤18000, PDI≤2.3), and high glass transition temperature (Tg≥160℃). With the increase of rigid structure content, the melting point of copolymers C1 and C3-C6 shows a trend of first decreasing and then increasing, the glass transition temperature gradually increases, while the crystallinity and tensile strength both show a trend of gradually decreasing.

[0111] It is worth noting that C1 exhibits a higher crystallinity retention capacity compared to C2. This may be related to the lower molecular weight and concentrated distribution of oligomer A2, which allows rigid structural units to periodically embed into the molecular chain during copolymerization, forming locally ordered regions, thus helping to maintain a certain level of crystallinity. With similar melting point reduction, higher crystallinity generally implies better mechanical properties, a fact also confirmed by tensile strength data.

[0112] Comparative Example 2 synthesized copolymer D via a one-step method, while this application synthesizes copolymers C1, C3-C6 via a two-step prepolymer-copolymer method. Both exhibit comparable properties in terms of melting point, glass transition temperature, crystallinity, and tensile strength.

[0113] Although copolymers C1 and D have similar ratios of rigid structural units (molar ratio of repeating units in Formula I to repeating units in Formula II = 80:20), the tensile strength of copolymer C1 is significantly higher than that of copolymer D. This may be because the different reactivity of the various bisphenol compounds in the one-step synthesis (polymer D) results in lower molecular chain regularity. However, this application utilizes a two-step prepolymer-copolymerization method, which can better achieve the periodic arrangement of structural units, thus helping to maintain the crystallinity and mechanical properties of the copolymer.

[0114] Furthermore, Comparative Examples 3 (E1) and 4 (E2) introduced amorphous segments (PEI) into polyetheretherketone (PEEK), which increased the glass transition temperature of the materials, while the melting point decreased due to the disruption of the crystalline structure. Although the tensile strength of E1 and E2 decreased only slightly, the decrease in melting point was limited, and the improvement in processing temperature was not significant.

[0115] The test results for the melting range are shown in Table 4 below.

[0116] Table 4: Melting Range Test of Products As shown in Table 4, with the increase of the amount of rigid cyclic structural units introduced, the melting range of copolymers C1-C4 gradually widens.

[0117] Interlayer bonding strength test of laser welded parts Part preparation: Preparation Example 1 (conventional PEEK) and C1 (modified copolymer) from Example 1 were used to injection mold 100×25×2mm sheets.

[0118] Overlap welding was performed using a semiconductor laser (wavelength 940nm): power 30W, speed 50mm / s, spot diameter 1.2mm.

[0119] Test method: Tensile shear strength: Prepare standard specimens (overlap area 10×5mm) according to ISO 19095-4.

[0120] The interface bonding was observed at the fracture cross section. The specific results are shown in Table 5 below.

[0121] Table 5: Performance Testing of the Part The test results above show that the modified material (polymer C1) according to this application reduces the welding temperature by 20°C while controlling the melt through a narrow melting range (ΔT=19.3°C), reducing interfacial crystallization defects, and increasing interlayer bonding strength by 26.8%. Therefore, the copolymer according to this application is particularly suitable for applications such as 3D printing and laser welding.

[0122] Some exemplary implementations are described below: Embodiment 1. A polyaryletherketone copolymer, wherein the polyaryletherketone copolymer satisfies the following properties: 1) The polyaryletherketone copolymer is substantially composed of the following: Repeating unit of Equation I: O Ph O Ph CO Ph (I), and Repeating unit of formula II containing a rigid ring structure: O Ph Ph O Ph CO Ph (II), and The repeating units of Formula I: The molar ratio of the repeating units of Formula I is 50:50 to 90:10, preferably 60:40 to 89:11, more preferably 60:40 to 85:15; and 2) The melting point of the polyaryletherketone copolymer is at most 332°C, preferably at most 325°C, more preferably at most 320°C, even more preferably at most 315°C, and most preferably at most 312°C.

[0123] Embodiment 2. The polyaryletherketone copolymer as described in Embodiment 1, wherein the number-average molecular weight of the polyaryletherketone copolymer is in the range of 15,000 to 45,000, and the molecular weight is determined by GPC.

[0124] Embodiment 3. The polyaryletherketone copolymer as described in Embodiment 1 or 2, wherein the rigid cyclic structure of the repeating unit of Formula II is derived from one or more of 2,2'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 1,4-naphthol, 1,5-naphthol, 2,3-naphthol, 2,6-naphthol, 2,7-naphthol, 2,2-bis(4-hydroxyphenyl)propane, and 4,4'-dihydroxydiphenyl sulfone, preferably derived from one or more of 2,2'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 1,4-naphthol, 1,5-naphthol, 2,6-naphthol, and 2,7-naphthol, more preferably derived from 4,4'-dihydroxybiphenyl.

[0125] Embodiment 4. The polyaryletherketone copolymer as described in any one of Embodiments 1 to 3, wherein the glass transition temperature of the polyaryletherketone copolymer is at least 150°C, preferably at least 155°C, and more preferably at least 160°C.

[0126] Embodiment 5. The polyaryletherketone copolymer as described in any one of Embodiments 1 to 4, wherein the melting range of the polyaryletherketone copolymer is at most 43°C, preferably at most 35°C, more preferably at most 30°C, even more preferably at most 25°C, and most preferably at most 23°C.

[0127] Embodiment 6. A polyaryletherketone copolymer as described in any one of Embodiments 1 to 5, wherein the repeating unit of Formula I has a structural formula shown in any one of Formulas (I-1) to (I-4): (I-1), (I-2) (I-3) (I-4) Preferably, the repeating unit of formula I has the structural formula shown in formula (I-1); The repeating unit of formula II has a structure shown in any one of the following formulas (II-1) to (II-7): (II-1) (II-2) (II-3) (II-4) (II-5) (II-6) (II-7) Preferably, the repeating unit of formula II has the structural formula shown in formula (II-1).

[0128] Embodiment 7. The polyaryletherketone copolymer as described in any one of Embodiments 1 to 6, wherein the tensile strength of the polyaryletherketone copolymer is at least 75 MPa, preferably at least 80 MPa, and more preferably at least 85 MPa, as determined according to GB / T1040.2-2022.

[0129] Embodiment 8. A method for preparing the polyaryletherketone copolymer according to any one of Embodiments 1-7, the method comprising the following steps: i) Under an inert atmosphere and in the presence of alkali metal carbonates, dihalobenzophenone undergoes nucleophilic condensation polymerization with a bisphenol derivative containing a rigid cyclic structure to obtain oligomer A; then ii) Under an inert atmosphere and in the presence of an alkali metal carbonate, oligomer A obtained in step i) is slowly added to a mixture of dihydroxybenzene, solvent, and dihalobenzophenone, and the reaction continues; then iii) After the reaction is completed, the mixture is cooled and purified to obtain the polyaryletherketone copolymer.

[0130] Implementation 9. The method as described in Implementation 8, wherein step i) is performed at a temperature of at least 220°C.

[0131] Implementation 10. The method as described in Implementation 8 or 9, wherein, in step i), there is at least 70% by weight of solvent relative to the total amount of feed, preferably at least 75% by weight of solvent, and more preferably at least 80% by weight of solvent.

[0132] Implementation Method 11. The method as described in any one of Implementation Methods 8 to 10, wherein the number average molecular weight of the oligomer A obtained in step i) is at most 18,000, preferably at most 16,000.

[0133] Implementation Method 12. The method as described in any one of Implementation Methods 8 to 11, wherein the polydispersity index of oligomer A obtained in step i) is at most 2.3, preferably at most 2.25, and more preferably at most 2.2.

[0134] Embodiment 13. The method as described in any one of Embodiments 8 to 12, wherein the glass transition temperature of the oligomer A obtained in step i) is at least 160°C, preferably at least 165°C, and more preferably at least 170°C.

[0135] Embodiment 14. A method for fused deposition modeling, wherein fused deposition modeling is performed using the polyaryletherketone copolymer described in any one of Embodiments 1 to 7 or the polyaryletherketone copolymer prepared by the method described in any one of Embodiments 8 to 13.

[0136] Embodiment 15. A printing material comprising the polyaryletherketone copolymer described in any one of Embodiments 1 to 7 or the polyaryletherketone copolymer prepared by the method described in any one of Embodiments 8 to 13, particularly a 3D printing material or a laser-weldable material.

[0137] Example 16. Use of the polyaryletherketone copolymer described in any one of Examples 1 to 7 or the polyaryletherketone copolymer prepared by the method described in any one of Examples 8 to 13 for the preparation of printing materials, particularly 3D printing materials, or laser-weldable materials.

[0138] Embodiment 17. A prepreg prepared from the polyaryletherketone copolymer described in any one of Embodiments 1 to 7 or the polyaryletherketone copolymer prepared by the method described in any one of Embodiments 8 to 13.

[0139] Although this application has been described with reference to numerous embodiments and examples, those skilled in the art will recognize from the disclosure of this application that other embodiments can be designed without departing from the protection scope of this application.

Claims

1. A polyaryletherketone copolymer, wherein the polyaryletherketone copolymer satisfies the following properties: 1) The polyaryletherketone copolymer is substantially composed of the following: The repeating unit of Equation I, and The repeating unit of formula II contains a rigid ring structure, and The molar ratio of repeating units in Formula I to repeating units in Formula II is 60:40 to 85:15; The repeating unit of Equation I has a structure shown in any one of Equations (I-1) to (I-4): (I-1), (I-2), (I-3), (I-4), The repeating unit of formula II has a structure shown in any one of the following formulas (II-1) to (II-7): (II-1), (II-2), (II-3), (II-4), (II-5), (II-6), (II-7); 2) The melting point of the polyaryletherketone copolymer is at most 312°C; 3) The glass transition temperature of the polyaryletherketone copolymer is at least 150°C; and 4) The melting range of the polyaryletherketone copolymer is at most 43°C; The polyaryletherketone copolymer is prepared by a method comprising the following steps: i) Under an inert atmosphere and in the presence of alkali metal carbonates, dihalobenzophenone undergoes nucleophilic condensation polymerization with a bisphenol derivative containing a rigid cyclic structure to obtain oligomer A; then ii) Under an inert atmosphere and in the presence of an alkali metal carbonate, oligomer A obtained in step i) is slowly added to a mixture of dihydroxybenzene, solvent, and dihalobenzophenone, and the reaction continues; then iii) After the reaction is completed, the mixture is cooled and purified to obtain the polyaryletherketone copolymer; Wherein, the number-average molecular weight of oligomer A obtained in step i) is at most 18,000.

2. The polyaryletherketone copolymer as described in claim 1, wherein, The number-average molecular weight of the polyaryletherketone copolymer is in the range of 15,000 to 45,000, and the molecular weight is determined by GPC.

3. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The glass transition temperature of the polyaryletherketone copolymer is at least 155°C.

4. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The glass transition temperature of the polyaryletherketone copolymer is at least 160°C.

5. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The melting range of the polyaryletherketone copolymer is at most 35°C.

6. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The melting range of the polyaryletherketone copolymer is at most 30°C.

7. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The melting range of the polyaryletherketone copolymer is at most 25°C.

8. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The melting range of the polyaryletherketone copolymer is at most 23°C.

9. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The repeating unit of Formula I has the structure shown in Formula (I-1); and the repeating unit of Formula II has the structure shown in Formula (II-1).

10. The polyaryletherketone copolymer of claim 1 or 2, wherein, The tensile strength of the polyaryletherketone copolymer is at least 75 MPa, as determined by GB / T1040.2-2022.

11. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The tensile strength of the polyaryletherketone copolymer is at least 80 MPa, as determined by GB / T1040.2-2022.

12. The polyaryletherketone copolymer as described in claim 1 or 2, wherein, The tensile strength of the polyaryletherketone copolymer is at least 85 MPa, as determined by GB / T1040.2-2022.

13. A method for preparing polyaryletherketone copolymers, the method comprising the following steps: i) Under an inert atmosphere and in the presence of alkali metal carbonates, dihalobenzophenone undergoes nucleophilic condensation polymerization with a bisphenol derivative containing a rigid cyclic structure to obtain oligomer A; then ii) Under an inert atmosphere and in the presence of an alkali metal carbonate, oligomer A obtained in step i) is slowly added to a mixture of dihydroxybenzene, solvent, and dihalobenzophenone, and the reaction continues; then iii) After the reaction is completed, the mixture is cooled and purified to obtain the polyaryletherketone copolymer; in, The number-average molecular weight of oligomer A obtained in step i) is at most 18,000; The polyaryletherketone copolymer satisfies the following properties: 1) The polyaryletherketone copolymer is substantially composed of the following: The repeating unit of Equation I, and The repeating unit of formula II contains a rigid ring structure, and The molar ratio of repeating units in Formula I to repeating units in Formula II is 60:40 to 85:15; The repeating unit of Equation I has a structure shown in any one of Equations (I-1) to (I-4): (I-1), (I-2), (I-3), (I-4), The repeating unit of formula II has a structure shown in any one of the following formulas (II-1) to (II-7): (II-1), (II-2), (II-3), (II-4), (II-5), (II-6), (II-7); 2) The melting point of the polyaryletherketone copolymer is at most 312°C; 3) The glass transition temperature of the polyaryletherketone copolymer is at least 150°C; and 4) The melting range of the polyaryletherketone copolymer is at most 43°C.

14. The method of claim 13, wherein, Step i) involves nucleophilic polycondensation at a temperature of at least 220°C.

15. The method of claim 13 or 14, wherein, In step i), there is at least 70% by weight of solvent relative to the total feed amount.

16. The method of claim 13 or 14, wherein, In step i), there is at least 75% by weight of solvent relative to the total feed amount.

17. The method of claim 13 or 14, wherein, In step i), there is at least 80% by weight of solvent relative to the total feed amount.

18. The method of claim 13 or 14, wherein, The number-average molecular weight of oligomer A obtained in step i) is at most 16,000.

19. The method of claim 13 or 14, wherein, The polydispersity index of oligomer A obtained in step i) is at most 2.

3.

20. The method of claim 13 or 14, wherein, The polydispersity index of oligomer A obtained in step i) is at most 2.

25.

21. The method of claim 13 or 14, wherein, The polydispersity index of oligomer A obtained in step i) is at most 2.

2.

22. The method of claim 13 or 14, wherein, The glass transition temperature of oligomer A obtained in step i) is at least 160°C.

23. The method of claim 13 or 14, wherein, The glass transition temperature of oligomer A obtained in step i) is at least 165°C.

24. The method of claim 13 or 14, wherein, The glass transition temperature of oligomer A obtained in step i) is at least 170°C.

25. A method of fused deposition modeling, wherein fused deposition modeling is performed using a polyaryletherketone copolymer as described in any one of claims 1 to 12 or a polyaryletherketone copolymer prepared by the method described in any one of claims 13 to 24.

26. A printing material comprising the polyaryletherketone copolymer of any one of claims 1 to 12 or the polyaryletherketone copolymer prepared by the method of any one of claims 13 to 24.

27. A 3D printing material comprising the polyaryletherketone copolymer of any one of claims 1 to 12 or the polyaryletherketone copolymer prepared by the method of any one of claims 13 to 24.

28. A laser-weldable material comprising the polyaryletherketone copolymer of any one of claims 1 to 12 or the polyaryletherketone copolymer prepared by the method of any one of claims 13 to 24.

29. Use of the polyaryletherketone copolymer according to any one of claims 1 to 12 or the polyaryletherketone copolymer prepared by the method according to any one of claims 13 to 24 for the preparation of printing materials.

30. Use of the polyaryletherketone copolymer according to any one of claims 1 to 12 or the polyaryletherketone copolymer prepared by the method according to any one of claims 13 to 24 for the preparation of 3D printing materials.

31. Use of the polyaryletherketone copolymer according to any one of claims 1 to 12 or the polyaryletherketone copolymer prepared by the method according to any one of claims 13 to 24 for the preparation of laser-weldable materials.

32. A prepreg prepared from the polyaryletherketone copolymer of any one of claims 1 to 12 or the polyaryletherketone copolymer prepared by the method of any one of claims 13 to 24.

Citation Information

Patent Citations

  • Preparation method of polyaryletherketone

    CN120365550A

  • Synthesis method of ternary copolymer containing PEDEK and PEEK using sulfolane as solvent

    CN1884330A